The economic impacts of tax-transfer policy : regional and distributional effects - Golladay, Fredrick L.; Haveman, Robert H.; Hollenbeck, Kevin (New York : Academic Press, 1977)
The study presented in this volume is intended to provide more general and hence more useful information about the impact of proposed reforms in income-maintenance programs on the size distribution of income
Includes bibliographical references and index.
osc 28/01/2019
Loans
Keywords: Negative income tax; Income distribution